The Diabetes Prevention Impact Tool Kit: An Online Tool Kit to Assess the Cost-Effectiveness of Preventing Type 2 Diabetes. Issue 5 (September 2019) - Lanza, Andrew; Soler, Robin; Smith, Bryce; Hoerger, Thomas; Neuwahl, Simon; Zhang, Ping
Abstract : The National Diabetes Prevention Program lifestyle change program demonstrated health benefits and potential for health care cost-savings. For many states, employers, and insurers, there is a strong business case for paying for type 2 diabetes prevention, which will likely result in medical and nonmedical cost-savings as well as improved quality of life after a few years. Using an iterative feedback process with multiple stakeholders, the Centers for Disease Control and Prevention developed the Diabetes Prevention Impact Tool kit, https://nccd.cdc.gov/toolkit/diabetesimpact, which forecasts the cost impact the lifestyle change program can have for states, employers, and health insurers. We conducted key informant interviews and a qualitative analysis to evaluate the tool kit. We found that end users recognized its utility for decision making. They valued the detail of the tool kit's underlying calculations and appreciated the option of either using the default settings or revising assumptions based on their own data. The Diabetes Prevention Impact Tool kit can be a helpful tool for organizations that wish to forecast the economic costs and benefits of implementing or covering the National Diabetes Prevention Program lifestyle change program.